Possessed - Wong, Bjarne; Sing, Sam Wong Ming ([Kuala Lumpur : Malaysia's Hock Star Entertainment, 2006)
Amber (Malay name Nurlin) and Lisu are two sisters from China, who have come to Malaysia to further their modelling and singing careers. One day Lisu goes missing, while Amber falls into a coma and is taken back to China for treatment. She awakens five months later with no memory of her past, and returns to Malaysia with her boyfriend, Dino. Amber decides to resume her modelling career and search for Lisu, but finds herself being harassed by an obsessive male fan and haunted by visions of her sister
Title from title screen
Special features: Trailer, photo gallery, making of possessed, interactive menus
Executive producers, Weng Heng Xue, Zhang san ; director of photography, Chau Kim Ming ; editor, Jeff Leong
Cast: Amber Chia, Harisu, Alan Yun, Steve Yap, Sharifah Amani, Liu Yan Yan, Smyth Wong, Manolet
DVD Format ; Dolby Digital
Optional subtitles in English, Malay or Chinese
Keywords: Ghosts -- Drama; Nightmares -- Drama; Murder -- Drama